Cyclic voltametric study of some alkyl substituted N-hydroxy-2, 6-diarylpiperidin-4-one semicarbazone and the antibacterial studies of the products. (2017) - Veeramalini, J.B.; Baskar, G.; Sheeja, N.
A series of 3-ethyl-2, 6-diarylpiperidin-4-one semicarbazone and 3, 5-dimethyl-2, 6-diarylpiperidin-4-one semicarbazone were synthesised. The semicarbazones were subjected to cyclic voltammetric analysis using glassy carbon electrode with variable scan rate. The method involves electron transfer without the use of oxidising or reducing agents. The study of cyclic voltammogram showed that all the compounds have undergone irreversible reduction. The peak potential values, the number of peaks formed during the anodic and cathodic scan and the different scan rate used have established irreversible reduction reaction. The reduction products were isolated and purified by column chromatography. The structure is proved by 1H and 13C NMR spectroscopy. Further five products were analysed for anti bacterial activity and the nitro substituted compound showed a high inhibition towards Salmonella typii among the eight bacterial cultures.